An improved CTC isolation scheme for pairing with downstream genomics: Demonstrating clinical utility in metastatic prostate, lung and pancreatic cancer. Issue 1 (28th September 2016) - Premasekharan, Gayatri; Gilbert, Elizabeth; Okimoto, Ross A.; Hamirani, Ashiya; Lindquist, Karla J.; Ngo, Vy T.; Roy, Ritu; Hough, Jeffrey; Edwards, Matthew; Paz, Rosa; Foye, Adam; Sood, Riddhi; et al.
Highlights: A two-step CTC enrichment process to improve the purity of CTCs is reported. Three different tumor types – prostate, lung and pancreas cancers – were evaluated. Average iCTC purity from spiked-in cancer cell lines increased from 0.2 to 79.1%. Average iCTC purity from metastatic cancer patients increased from 0.3 to 80.1%. High purity iCTCs were compatible with various downstream genomic analyses. Abstract: Improvements in technologies to yield purer circulating tumor cells (CTCs) will enable a broader range of clinical applications. We have previously demonstrated the use of a commercially available cell-adhesion matrix (CAM) assay to capture invasive CTCs (iCTCs). To improve the purity of the isolated iCTCs, here we used fluorescence-activated cell sorting (FACS) in combination with the CAM assay (CAM + FACS). Our results showed an increase of median purity from the CAM assay to CAM + FACS for the spiked-in cell lines and patient samples analyzed from three different metastatic cancer types: castration resistant prostate cancer (mCRPC), non-small cell lung cancer (mNSCLC) and pancreatic ductal adenocarcinoma cancer (mPDAC). Copy number profiles for spiked-in mCRPC cell line and mCRPC patient iCTCs were similar to expected mCRPC profiles and a matched biopsy. A somatic epidermal growth factor receptor (EGFR) mutation specific to mNSCLC was observed in the iCTCs recovered from EGFR + mNSCLC cell lines and patient samples. Next-generation sequencing (NGS) of spiked-in pancreatic cancer cell line and mPDAC patient iCTCs showed mPDAC common mutations. CAM + FACS iCTC enrichment enables multiple downstream genomic characterizations across different tumor types.